Quadriceps muscle fat infiltration is associated with cardiometabolic risk in COPD. (3rd November 2017) - Vivodtzev, Isabelle; Moncharmont, Luc; Tamisier, Renaud; Borel, Jean‐Christian; Arbib, François; Wuyam, Bernard; Lévy, Patrick; Maltais, François; Ferretti, Gilbert; Pépin, Jean‐Louis
Summary: Purpose: Losses of peripheral muscle mass and ectopic fat accumulation have been associated with cardiometabolic morbidity in COPD. We aimed at identifying the relationship between quadriceps muscle fat infiltration and cardiovascular risk. Materials and methods: From 2009 to 2014, 78 COPD patients (64 ± 8 years; 80% male) were prospectively included after having given written consent (ethical committee approval number: 2006‐A00491‐50). The cohort was divided into three groups (tertiles) according to body mass index (BMI), low [15 < BMI≤23·3], middle [23·3 < BMI≤27·6] and high [27·6 < BMI≤36] kg/m²). Measurements were respiratory function, plasmatic biomarkers and surrogate markers of cardiovascular risk (arterial stiffness and endothelial function). Mid‐thigh quadriceps muscle volume and per cent of muscle fat infiltration, as assessed by 64‐slice CT scanning, were compared between the tertiles. ANOVA or Kruskal–Wallis tests were used for statistical analyses with Bonferroni's correction for the 'post hoc' tests. Results: Intramuscular fat volume was 52% [95% CI, 43 to 60%] of total quadriceps volume in high BMI vs. 47% [38 to 55%] and 34% [29 to 38%] in the middle and low‐BMI groups, respectively ( P <0·0001), without differences between groups in fat‐free muscle volumes. Elevated muscle fat infiltration correlated with lower thiol to protein ratios in the whole population reflecting impaired antioxidant capacity ( r = 0·50; P = 0·009). Furthermore, muscle fat infiltration was linked to endothelial dysfunction ( r = −0·49, P = 0·01) in the low‐BMI group. Conclusion: Skeletal muscle fat infiltration may be an indicator of increased cardiometabolic risk in both obese and lean COPD patients.